Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan Di Faperta IPB - Riski, Muhamad (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
The purpose of this study was to influence of leadership style and work discipline on employee performance at Faperta IPB. This type of research is quantitative. The population of this study were employees at Faperta IPB. The analysis used is Structural Equation Modeling (SEM) analysis using the SmartPls 4 data processing application, hypothesis testing and the coefficient of determination. The number of samples in this study took 60 respondents. The research instrument was a questionnaire using the Google form. This study shows that the variable of leadership style has no significant effect on employee performance at Faperta IPB, work discipline has a significant effect on employee performance at Faperta IPB, leadership style has an effect on work discipline at Faperta IPB and leadership has an effect on employee performance through work discipline variables at Faperta IPB. It is hoped that from the results of this research the leadership of Faperta IPB will continue to develop their leadership style and that Faperta IPB employees will continue to improve their work discipline to get maximum performance.